The Unobserved Heterogeneity Distribution in Duration Analysis - Jaap H. Abbring; Gerard J. van den Berg (Tinbergen Institute, 2006)
In a large class of hazard models with proportional unobserved heterogeneity, the distribution of the heterogeneity among survivors converges to a gamma distribution. This convergence is often rapid. We derive this result as a general result for exponential mixtures and explore its implications for the specification and empirical analysis of univariate and multivariate duration models.
Keywords: C41; C14; 330; duration analysis; exponential mixture; gamma distribution; limit distribution; mixed proportional hazard; Ökonometrie; Moral Hazard; Statistische Bestandsanalyse